Reforming College Sports and a Constrained, Conditional Antitrust Exemption. (15th June 2016) - Zimbalist, Andrew
Abstract : This paper argues that intercollegiate athletics is at a turning point. The status quo is not stable and change is coming. This change can move college sports further toward commercialization and quasi‐professionalism or it can endeavor to reinforce the historical vision of college sports as an amateur activity subordinated to the educational mission of U.S. colleges. The former path will lead to increasing academic scandals, widespread financial insolvency and diminishing support for Olympic sports and Title IX. The latter path, while not without its own challenges, may succeed in restoring a proper balance between athletics and academics. Copyright © 2016 John Wiley & Sons, Ltd.